Drylan Swimming Workout Di Masa Pandemi - Ari Priana; Abdul Narlan; Agus Arief Rahmat; Yuniarti Sani Damayanti (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
During the pandemic, the closure of public facilities including swimming pools became a complex problem for the development of swimming sports because especially in Indonesia swimming training still uses public facilities so that it can no longer exercise swimming as usual. Researchers who are also coaches at one of the swimming clubs, are required to provide solutions to the problem. Dryland Swimming Workout was created and developed by researchers who aim to create a series of movements for the exercise of the dominant physical condition in swimming sports conducted on land and combined with the overall swimming movement series as a swimming exercise option if it must be done on land. The research methods used in this study use research and development (R&D) methods. The creation of a Dryland Swimming Workout series for the exercise of the dominant physical condition in swimming is made in the form of a video in which there is a series of motions, instructions, and tools that can be used to perform Dryland Swimming Workout. The forms of movement contained in Dryland Swimming Workout include front streamline, jumping jacks, freestyle, high elbow push up rotation, braest stroke squat, braest stroke, sit up, high knee, back streamline, back stroke, dips, squat thrust, butterfly stroke, butterfly back raise.